Providing Education on Excellent Service Skills for Female Students of Hidayatullah Islamic Vocational School in Batam City Indonesia - Lapotulo, Nensi; Sukmamedian, Haufi; Afriani, Miratia (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This community service initiative focuses on imparting essential service skills to female students of Hidayatullah Islamic Vocational School in Batam City, Indonesia. Recognizing the significance of excellent service in various professional spheres, particularly in the context of a rapidly evolving global economy, this program aims to empower young women with the knowledge necessary to excel in service-oriented roles. Through a series of interactive education, participants are equipped with fundamental service principles, communication techniques, and interpersonal skills. Moreover, emphasis is placed on instilling confidence, resilience, and a strong sense of professionalism among the students, enabling them to navigate challenges and seize opportunities in the dynamic service industry. By fostering a culture of excellence and service-mindedness, this initiative not only enhances the prospects of the participants but also contributes to the socio-economic development of the community at large. Through collaborative efforts with participants and educational institutions, this program seeks to foster a supportive environment acquire valuable skills, knowledge, and confidence to succeed in service-oriented roles in Batam City in general and at school in particular.